Throwing with different kinetic chains - Stirn, I.; Strojnik, V. (Biomechanics and Medicine in Swimming X, 2006)
Overarm throw is determined by a so called proximal-to-distal principle (9). Our concept of studying kinetic chain was to gradually add the active muscles in the throwing kinetic chain, and measure the throwing velocity. Doing so, the contribution of the newly added muscles to the final velocity of the ball can be estimated. As kinetic chain was prolonged from P1 to P3 Position, the throwing velocities increased with both normal and heavy ball. However, in water throw (P4) normal ball velocity was additionally increased while in heavy ball decreased, very likely due to insufficient leg/pelvis stabilization in water during heavy ball throw. On individual basis, players playing in different positions (driver, center-forward, goalkeeper) had different velocity increase due to changed kinetic chain.